Adaptive K-Repetition Transmission Employing Site Diversity Reception for 5G NR Uplink Grant-Free URLLC - Arif Dataesatu; Kosuke Sanada; Hiroyuki Hatano; K. Mori; Pisit Boonsrimuang (My University, 2023)
The Internet of Things (IoT) is currently being employed for wireless real-time interactive systems with ultra-reliable and low-latency communications (URLLC) that provide high service quality for the fifth generation (5G) new radio (NR) standard. Grant-free (GF) transmission with K-Repetition (K-Rep) is a transmission technique that aims to meet the URLLC requirements. However, the K-Rep increases the number of packet transmissions, which may cause severe interference and substantial energy consumption. This paper employs site diversity reception to the GF K-Rep scheme and proposes its adaptive control mechanism to decrease the number of repeated transmissions in order to improve communication reliability and energy consumption for IoT URLLC users. According to our simulation results, the proposed site diversity reception for the K-Rep scheme can significantly improve the reliability compared with the conventional K-Rep under single-cell reception. Additionally, the proposed adaptive K-Rep control scheme can reduce the transmission energy consumption greatly, hence saving battery resource of IoT URLLC users.
Keywords: Cooperative Communication and Network Coding; Advanced MIMO Systems Optimization; Advanced Wireless Communication Technologies